Exact repetition in grammar and discourse - Finkbeiner, Rita; Freywald, Ulrike (Trends in linguistics. Studies and monographs ;, 2018)
Most scholars define reduplication as a formally restricted grammatical process, neatly distinguishing it from 'mere' repetition as a discoursal option. However, there is a fuzzy grey area between the two processes that has rarely been explored so far. In this timely collection, the phenomenon of exact repetition, understood broadly as the systematic iteration of one and the same linguistic item within relatively close syntactic proximity, is investigated from a number of angles. The volume contains studies from phonology, morphology, syntax, semantics, and pragmatics, and deals with a broad range of languages, including alleged 'reduplication avoiders'. In bringing together different theoretical perspectives, phenomenological domains, and methodologies, and in linking the fields of syntax and discourse to those of morphology and morphophonology, the volume provides new insights into the structure and meaning of exact repetition phenomena, and, more generally, into their status within a theory of language. The collection will appeal to formally and functionally oriented scholars from all subfields of linguistics, including typology.